Do Buffer Zone Programs Improve Local Livelihoods and Support Biodiversity Conservation? The Case of Sagarmatha National Park, Nepal. (30th May 2022) - Silwal, Thakur; Devkota, Bishnu P.; Poudel, Prabin; Morgan, Mark
Background and Research Aims: Buffer zone programs aim to reduce park-people conflicts by improving local livelihoods through integrated conservation and development activities. A case study was conducted at Sagarmatha National Park, Nepal from 2002–2016 to examine some buffer zone initiatives. Methods: Focus group discussions ( n = 7), key informant interviews ( n = 14), and field observations were performed in accordance with the IUCN Framework for Assessing Management Effectiveness of Protected Areas 2006 and WWF´s Rapid Assessment and Prioritization of Protected Area Management 2006. Results: A total of 99 buffer zone activities were identified, including a variety of construction activities such as hydroelectric projects, trails, schools, and monasteries. Park funds were allocated mainly for community development and social welfare (42%), and less on conservation and conflict management (22%). For example, traditional " Nawa " animal rearing practices, feral dog control, and mitigation of wildlife damages to crops and livestock were overlooked. Conclusion: Support gained from the buffer zone program to address livelihoods of needy households who suffer from wildlife damages was lacking, despite legal provisions for compensation (e.g. crop damages caused by jharal ). This should not occur at the expense of wildlife conservation and if it does, it will diminish the original intent of buffer zones. Implications for Conservation: Although most of the local communities were positive about buffer zone programs and activities, there was a dire need to incorporate " Nawa " practices, wildlife damage compensation schemes, and feral dog controls. This study suggests to update policies that focus on conflict management.